Transcriptome analyses reveals the dynamic nature of oil accumulation during seed development of Plukenetia volubilis L. - Guo Liu (Nature Portfolio, 2020)
Abstract Sacha inchi (Plukenetia volubilis L.) is a shrub native to Amazon rainforests that’s of commercial interest as its seeds contain 35–60% edible oil (dry weight). This oil is one of the healthiest vegetable oils due to its high polyunsaturated fatty acid content and favourable ratio of omega-6 to omega-3 fatty acids. De novo transcriptome assembly and comparative analyses were performed on sacha inchi seeds from five stages of seed development in order to identifying genes associated with oil accumulation and fatty acid production. Of 30,189 unigenes that could be annotated in public databases, 20,446 were differentially expressed unigenes. A total of 14 KEGG pathways related to lipid metabolism were found, and 86 unigenes encoding enzymes involved in α-linolenic acid (ALA) biosynthesis were obtained including five unigenes encoding FATA (Unigene0008403), SAD (Unigene0012943), DHLAT (Unigene0014324), α-CT (Unigene0022151) and KAS II (Unigene0024371) that were significantly up-regulated in the final stage of seed development. A total of 66 unigenes encoding key enzymes involved in the synthesis of triacylglycerols (TAGs) were found, along with seven unigenes encoding PDCT (Unigene0000909), LPCAT (Unigene0007846), Oleosin3 (Unigene0010027), PDAT1 (Unigene0016056), GPDH (Unigene0022660), FAD2 (Unigene0037808) and FAD3 (Unigene0044238); these also proved to be up-regulated in the final stage of seed development.